Effects of methyl parathion on Oscimum americanum L. infected with fungus Fusarium oxysporum - Mishra, K.K. (Nepalese Journal of Biosciences, 2013)
The pathogen Fusarium oxysporum during its different stages of growth-mycelia, mat of mycelia, microconidia and megaconidia-liberates several toxic substances that either inactivate the cells or lysis of even xylem and phloem tissues of the host plant Oscimum americanum.